Analysis of user satisfaction of e-learning systems in Uganda using DeLone and McLean model - Patience Atukunda; Simon Peter Khabusi; John Othieno (Springer, 2024)
Abstract This study investigates user satisfaction with e-learning systems in higher education institutions, examining the perspectives of students, lecturers, and elearning officers and heads of the department of Information Technology as key informants. A total of 375 student respondents from Diploma, Bachelor, and Masters levels, 51 lecturers, and 15 key informants across different Ugandan institutions of higher learning participated in the study, providing insights into platform usage, system usability, stability, and support mechanisms. Rigorous analysis techniques, including means, correlation coefficient calculations, were employed to explore factors influencing satisfaction. Findings revealed positive correlations between satisfaction and variables such as ease of use, ease of access, system reliability, system stability, and prompt response to queries, among others. Recommendations include improving system stability, enhancing response time to queries, providing ongoing training, addressing connectivity issues, and developing customized mobile applications. The study highlights the need for institutions to optimize e-learning experiences by leveraging feedback from users and implementing targeted interventions.